PERAN PENDIDIKAN ANAK USIA DINI (PAUD) DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI TAMAN AGUSTUS - Purnamasari, Frieska (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT Character education is very important for early childhood in shaping his personality. Teaching children character education can be applied at the Institute of early childhood education. The role of early childhood education and have one role that is developing the potential of each child by his protégé to be able to grow and develop in accordance with his age. The formation of character in children can be analyzed through the study of sociology education. This research seeks to discuss about the process of formation of characters that occur in children aged 3-6 years in the Taman Agustus through roles and learning model Taman Agustus. Based on the results of the research, that the establishment of the characters contained in the Taman Agustus using a descriptive esxploratory research method through the analysis of the theory of the self according to Herbert Mead which is divided into four stages, namely the stage preparatory stage, play stage, game stage, and generalize other. Preparatory stage can be studied through the pronunciatiation of the words correctly as the word ‘puyang’ which means ‘pulang’. Play stage can be indicated that the child begins to realize about his identity and his family as well as the child begins to understand about the activity of others against him. According to Mead, game stage is not to think of yourself in achieving a specific goal. Whereas the Generalize phase for a child is already beginning to understand the role to they each like to wear school uniform on the schedule, asking permission to the toilet without being accompanied by another person, and children have become self-sufficient, disciplined, honest, et cetera. There are always barriers for care givers in educating young learners including, those difable children in special need and lack of teaching staff. Therefore, it is expected that more teachers still being are patient and give more attention to the children in a need special. In addition, to that it is recommended to school principals and teachers the increasing quality of teaching staff that prioritizes parenting and educating experience in early childhood. Updates are more effective in shaping the character of early childhood education in Taman Agustus. Keywords: Early Childhood, Character, Role, Early Childhood Education